MOCVD of GaN-based HEMT structures on 8 inch silicon substrates. Issue 1736 (11th February 2015) - Laboutin, Oleg; Lo, Chien-Fong; Kao, Chen-Kai; O'Connor, Kevin; Johnson, Wayne; Hill, Daily
ABSTRACT: Metal organic chemical vapor deposition, as well as material and basic device properties of nitride-based high electron mobility transistor structures on (111) silicon substrates varying in diameter from 4 to 8 inch were studied using in-situ and ex-situ characterization techniques. All substrates used for the growth of the nitride structures in this study were of SEMI standard thicknesses. The total thickness of the nitride structures was in the range of 1.5 – 5 µm. It is reported that nitride structures can be grown on 4, 6 and 8 inch diameter substrates with very similar post-growth wafer shape, material and device characteristics. It is also shown that their crystal quality, 2DEG transport properties and isolation blocking voltages can be improved by increasing nitride structure thickness while maintaining post-growth wafer bow and warp less than 50 µm. The maximum thickness of nitride structures that can be successfully grown on 8 inch diameter SEMI standard substrates seems to be limited to about 4.5 µm due to plastic deformation of Si. Blocking voltages of more than 700 V were achieved using 4.5 µm thick nitride-based high electron mobility transistor structures grown on 8 inch Si substrate.